Temperature-Responsive Micro-Cross-Linking: A Novel Solution for Enhancing High-Temperature Viscosity and Settlement Stability of High-Density Cement Slurry - Lifang Song; Chengwen Wang; Jingping Liu; Dingye Li (Gels)
In order to solve the problem of solid-phase particle settlement of high-density cement paste used in deep/ultra-deep wells, a temperature-responsive micro-cross-linking method was innovatively adopted to increase the viscosity and settlement stability of high-density cement paste at high temperatures. Through the self-developed suspension stabilizer and cross-linking agent to form micro-cross-linking gel at high temperature, the increase in high-temperature viscosity of cement paste was successfully realized without increasing the low-temperature viscosity of cement paste. Moreover, this micro-cross-linking reaction, together with the hydrophobic binding effect of the suspension stabilizer, strengthened the filamentary linkage network structure in the polymer solution with the formation of a lamellar linkage network structure. This effectively compensated for the decrease in viscosity of the polymer solution with increasing temperature. The results show that the micro-cross-linked system can be successfully cross-linked at elevated temperatures of 120–220 °C in pH 8–13 and salt content of 0–10%. The viscosity of the micro-cross-linked system was 144.5 mPa·s after 20 min at 220 °C with a shear rate of 170 s−1, which was 91% higher than the viscosity of the un-cross-linked system. After curing at 220 °C, the density difference between the top and bottom of the high-density cement was 0.025 g/cm3, which was 84% lower than the un-cross-linked system. This helped the high-density cement slurry to maintain the homogeneity of the components at high temperatures and ensured the high-temperature consistency and suspension stability of the slurry. This study helps to improve the cementing effect of deep/ultra-deep wells and provides a new method to solve the problems of cement slurry settlement and destabilization under high-temperature and high-pressure well conditions.